What makes microfinance happen? - Jiménez Castillo, Manuel Antonio (2015)
In this paper we have attempted to shed light on what makes development happen from those determinants that enable microfinance work as an effective tool to eradicate poverty. The effectiveness of such instrument in the generation of wealth to the poorest class demand overcoming the minimalist approach that condemns its practices to a mere provision of microfinancial services. This hypothesis will be analytically and empirically proven assuming human development as a cause and not only as an outcome of the microfinance success. To such end, two regression lines were designed where variables such as education, health and food security proved to be explanatory determinant to explain income behaviour for those beneficiaries of the microfinance programs.